Penatalaksanaan Emesis Gravidarum pada Ny. H G3P2A0 Umur 31 Tahun dengan Pijat Akupresur - Sari, Lidia Ratna; Sofiyanti, Ida (Universitas Ngudi Waluyo, 2025)
Emesis Gravidarum is a symptom of nausea accompanied by vomiting that occurs in early pregnancy (Niebyl, 2010). The cause of emesis gravidarum is increased levels of the hormones Estrogen, Progesterone and Human Chorionic Gonodothropine (HCG). Nausea and vomiting in pregnancy are often also called